An extraction method for nitrogen isotope measurement of ammonium in a low-concentration environment - A. Lamothe; J. Savarino; P. Ginot; L. Soussaintjean; E. Gautier; P. D. Akers; N. Caillon; J. Erbland (Atmospheric Measurement Techniques, 2023)
Ammonia (NH 3 ) participates in the nucleation and growth of aerosols and thus plays a major role in atmospheric transparency, pollution, health, and climate-related issues. Understanding its emission sources through nitrogen stable isotopes is therefore a major focus of current work to mitigate the adverse effects of aerosol formation. Since ice cores can preserve the past chemical composition of the atmosphere for centuries, they are a top tool of choice for understanding past NH 3 emissions through ammonium (NH 4 + ) <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="12pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="1d1df68cc0babb91d0019908a6c0308d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-4015-2023-ie00001.svg" width="12pt" height="15pt" src="amt-16-4015-2023-ie00001.png"/></svg:svg> , the form of NH 3 archived in ice. However, the remote or high-altitude sites where glaciers and ice sheets are typically localized have relatively low fluxes of atmospheric NH 4 + <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="aa378b71f34a6c23384fc0eb7c6e7621"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-4015-2023-ie00002.svg" width="8pt" height="15pt" src="amt-16-4015-2023-ie00002.png"/></svg:svg> deposition, which makes ice core samples very sensitive to laboratory NH 3 contamination. As a result, accurate techniques for identifying and tracking NH 3 emissions through concentration and isotopic measurements are highly sought to constrain uncertainties in NH 3 emission inventories and atmospheric reactivity unknowns. Here, we describe a solid-phase extraction method for NH 4 + <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="e480ef7ec07e999cc23d83cf2e7b4868"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-4015-2023-ie00003.svg" ...